Pemberdayaan Administrasi Perwakafan Di Desa Mekarsari Kabupaten Sumedang - Neni Nuraeni; Nandang Najmudin (LPPI UMN AL WASHLIYAH, 2025)
In Mekarsari Village, Sumedang Regency, the registration of waqf land is a persistent problem because many people have donated their property, yet it has not been properly certified. Many people still don't understand how to register land waqf. This will be detrimental to many parties if the waqf land leads to disputes. This service aims to determine the level of understanding of land waqf administration in Mekarsari Village using the Participatory Action Research (PAR) approach, which is an approach aimed at learning to overcome problems and meet the practical needs of the community, as well as producing knowledge and the process of socio-religious change. From the community service activities carried out, it was found that the residents of Mekarsari Village can understand land ownership administration well. The socialization conducted raises awareness among the residents of Mekarsari village to prioritize administrative order in land waqf. The discussion regarding the provisions for waqf land certification was understandable to representatives of the majelis ta'lim groups and several educational institutions from the Mekarsari village community, as well as their commitment to actively and supportively engage with the various dynamics of waqf in society. The community is also able to understand the implications that arise if there is no written evidence in the form of certificates, AIW, or a replacement deed for the deed of waqf (hereinafter referred to as APAIW).